Introduction to NJWLS 2019-3 - Buch, Anders (Nordic Journal of Working Life Studies, 2019)
This issue of Nordic Journal of Working Life Studies consists of four articles and a book review that thematize and discuss issues of working life in the Nordic countries from various angles (...)